PENINGKATAN PEMAHAMAN TEKNOLOGI INFORMASI DALAM MENDUKUNG PEMBELAJARAN DARING - Rodame Monitorir Napitupulu (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
Online learning is currently an inseparable part of the learning system since the COVID-19 pandemic. One of the obstacles in carrying out online learning is the limited skills in using information technology. This community service aims to improve students' understanding of information technology in supporting online learning. Based on the Pre and Post Test analysis, there was an increase in basic knowledge of information technology by 2.8% - 5.6% while an increase in understanding of the use of information technology was 8.3% - 13.9%. Overall there is an increase in knowledge and understanding of information technology after the training.